The Role of the Tahfidz Extracurricular Program in Fostering Character Education at SMK Muhammadiyah 1 Sukoharjo - Jannah, Aisyah Nur Kholifatun; Shobahiya, Mahasri (Electronic Journal of Education, Social Economics and Technology, 2025)
This study focuses on the tahfidz extracurricular activities at SMK Muhammadiyah 1 Sukoharjo, aiming to maintain the memorization of students who already had a foundation before entering the school. This study aims to: (1) describe character education through tahfidz extracurricular activities; and (2) analyze the purpose of implementing tahfidz extracurricular activities at the school. This research uses a descriptive qualitative method with the study conducted at SMK Muhammadiyah 1 Sukoharjo, Sukoharjo District, Sukoharjo Regency. The research was conducted on January until February 2025. Data collection techniques include interviews, documentation, and observation. The results of the study indicate that: (1) The tahfidz extracurricular activities can foster character education continuously and dynamically, shaping positive habits in students; and (2) In an effort to maintain memorization through tahfidz extracurricular activities, the school strives to create an effective schedule and methods so that students can participate without obstacles, providing a positive influence on the development of students' character.